Literature Study on Zakat: Compilation of Factors Hindering Zakat Collection in Indonesia - Muhamad Ramdhani Jihad; Isman Isman; Wardah Yuspin (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The high potential for zakat in Indonesia cannot be separated from the obstacles to its collection. This study aims to analyze and compile various factors that hinder the collection of zakat in Indonesia based on the results of a literature review of various previous studies. The method used is a literature review by examining scientific articles, zakat institution reports, relevant academic publications in the period 2020-2025, as well as through interviews with relevant and knowledgeable sources on zakat issues in their surroundings. The results of the study show that low public awareness and literacy regarding zakat, lack of trust in Zakat Institutions, the quality of Amil human resources, uneven governance and infrastructure, legal obstacles, and the dual function of BAZNAS are the biggest factors hindering zakat collection in Indonesia. This research contributes to strengthening the national zakat collection strategy by emphasizing the importance of increasing public literacy and awareness of zakat, along with improving the quality of Zakat Institutions to strengthen public trust, and strengthening collaboration between the government, BAZNAS, and Zakat Institutions (LAZ) in Indonesia.